Characterisation of composite skin–stiffener bonding interface and fine-defect evaluation using mono-pulse ultrasonic detection. (October 2022) - Liu, Feifei; Zhou, Zhenggan; Liu, Songping; Li, Legang; Fu, Tianhang; Chang, Haifeng
Abstract: A mono-pulse ultrasonic (MU)-based detection method was developed for the detailed characterisation of the carbon-fibre skin–stiffener bonding interface and the quantitative evaluation of the fine defects therein. Specimens exhibiting artificial defects and actual skin–stiffener components were used as test specimens. A MU experimental system was constructed. Experiments were performed to elucidate reflection behaviour and signal and morphological characteristics of skin–stiffener joints, and the microstructural morphologies were compared. Defect detectability was experimentally studied at different sample depths. The results showed that the reflected-signal pulse width was ∼1 period. The ultrasonic dead zone reached a single pre-preg-ply thickness (∼ 0.125 mm). The de-lamination, de-bonding, adhesive and resin layers, and changes in the bonding-interface layup, were well determined. The minimum and maximum deviations of the detected-defect sizes were ∼ 0.0 and 1.0 mm, respectively. The de-lamination depth-positioning deviation was < 0.5 of a pre-preg ply. Graphical abstract: Image 1 Highlights: Skin–stiffener bond interface characterised using mono-pulse ultrasonic detection. Fine defects quantitatively evaluated using mono-pulse ultrasonic detection. De-lamination, de-bonding, and adhesive/resin layers are reliably determined. Minimum/maximum deviations in detected-defect sizes are ∼ 0.0/1.0 mm, respectively. Deviation in de-lamination depth positioning is < 0.5 pre-preg ply.